Isolation, identification, and characterization of the nematophagous fungus Monacrosporium salinum from China. (1st April 2015) - Liu, Wei; Han, Yuan; Wang, Bo‐bo; Sun, Long‐jie; Chen, Ming‐yue; Cai, Kui‐zheng; Li, Xuan; Zhao, Ming‐wang; Xu, Chun‐lan; Xu, Qiang; Yi, Lin‐xin; Wang, Hui; et al.
<x xml:space="preserve">Abstract</x> Nematophagous fungi are considered to have the best potential as biological agents for the control of gastrointestinal nematodes in domestic animals. However, relatively few studies have been conducted with the genus Monacrosporium, especially with strains native to China. In the present study, we isolated and identified nematophagous fungi from fresh sheep feces. A pure fungal strain was molecularly characterized, and its nematophagous activity was evaluated. The morphological plasticity of the isolated strain, as well as its interaction with the nematode targets, was observed by scanning electron microscopy of the infected Trichostrongylus colubriformis L3 and the free‐living nematode Caenorhabditis elegans. Three isolated fungal strains from the 30 fresh fecal samples of sheep from Inner Mongolia, China exhibited predatory activity; however, only a single strain was successfully purified (SF 0459). The SF 0459 strain was characterized by morphological analysis of its conidia and sequencing of its ITS1–5.8S rDNA–ITS2 region. This strain was identified to be Monacrosporium salinum (GenBank ID: KP036623). Nematophagous fungus helper bacteria were found at the interaction points between fungi and nematodes. The percentage of live T. colubriformis L3 was reduced by 83.79–88.69% based on the in vitro assay.